Enhanced dechlorination of 2, 4‐dichlorophenoxyacetic acid by Pd/Fe nanoparticles in the presence of environment‐friendly iminodisuccinic acid. (8th October 2018) - Zhou, Hongyi; Zhao, Yongkang; Xiang, Junchao; Baig, Shams Ali; Chen, Yong
Abstract : Environment‐friendly iminodisuccinic acid (IDS) has been recognized to enhance the reactivity of Pd/Fe nanoparticles (nPd/Fe) for the effective dechlorination of 2, 4‐dichlorophenoxyacetic acid (2, 4‐D). In this study, the improving effects of IDS and other experimental parameters, such as IDS concentration, initial pH, Pd ratio and reaction temperature, on the reduction of 2, 4‐D were investigated. Characterization analyses of nPd/Fe with and without IDS were performed, and the mechanism of the improvement by IDS of nPd/Fe reactivity was also elucidated. Results revealed that IDS not only removed the passivation layer on nanoscale zero‐valent iron (nZVI) surface, but also inhibited the iron ions from forming nZVI surface passivation layer through complexation. As a result, nPd/Fe maintained their reactivity throughout the reaction. In the presence of IDS, the removal efficiency of 2, 4‐D by nPd/Fe was significantly increased from 32.5 to 99.2%, and nearly 96.2% phenoxyacetic acid (PA) was simultaneously generated. The findings from the present study demonstrate that IDS could be a promising alternative complexing agent for inhibiting surface passivation and enhancing the effective utilization of nPd/Fe for dechlorination. Abstract : High reactivity of Pd/Fe nanoparticles is obtained through reacting passivation layers on the particle surface and free iron ions in aqueous solution with biodegradable iminodisuccinic acid, which can be used to very effectively dechlorinate 2, 4‐dichlorophenoxyacetic acid.